Novel glass ceramic foams materials based on polishing porcelain waste using the carbon ash waste as foaming agent - Guo, Yuxi; Zhang, Yihe; Huang, Hongwei; Meng, Xianghai; Liu, Yangyang; Tu, Shuchen; Li, Baoying (Construction & building materials, 2016)
•Glass ceramic foams have been prepared based on polishing porcelain waste and carbon ash.•Increasing the amount of carbon tends to cause coalescence.•Lowering sintering temperature or reducing holding time avoids cell coalescence. This study reports on the feasibility of producing glass ceramic foams using polishing porcelain waste as a major raw material from ceramic industry, as well as waste carbon ash as an alternative carbon-based foaming agent derived from recycled metal industry. Initial batch composition and temperature process parameters were tuned to investigate its effect on properties such as bulk density, compressive strength. The cellular microstructure of glass ceramic foams was characterized by scanning electron microscopy (SEM). Structural characterization by X-ray diffraction measurement revealed the amorphous or crystalline phases depending on process parameters. Polishing porcelain waste can be successfully recycled by adding 2wt.% carbon ash to produce relatively low weight foams in the optimum foaming temperature range 1030–1080°C. The apparent density of the foams ranged from 0.29 to 0.37g/cm3, and the compressive strength ranged from 1.32 to 2.88MPa. The experimental compositions allowed recycling residues to produce sintered glass ceramic foams with suitable properties with environmental benefits.